2014
DOI: 10.1371/journal.pone.0090169
|View full text |Cite
|
Sign up to set email alerts
|

Renal Failure in Lithium-Treated Bipolar Disorder: A Retrospective Cohort Study

Abstract: ObjectiveLithium users are offered routine renal monitoring but few studies have quantified the risk to renal health. The aim of this study was to assess the association between use of lithium carbonate and incidence of renal failure in patients with bipolar disorder.MethodsThis was a retrospective cohort study using the General Practice Research Database (GPRD) and a nested validation study of lithium exposure and renal failure. A cohort of 6360 participants aged over 18 years had a first recorded diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 30 publications
6
62
1
Order By: Relevance
“…As suggested recently by Close et al (2014) and supported by Bocchetta et al (2015), absorption of Li occurs completely in the gastrointestinal tract and filtered through the glomeruli then reabsorbed in the proximal tubule which represents the primary site at which the reabsorption process occurs. It accumulates in the collecting tubule and interferes with capacity of the collecting tubule (especially the cortical portion) in both kidneys to generate cyclic adenosine monophosphate as response of stimulation of antidiuretic hormone (Erden et al 2013;Oruch et al 2014;Clos et al 2015).…”
Section: Introductionmentioning
confidence: 73%
“…As suggested recently by Close et al (2014) and supported by Bocchetta et al (2015), absorption of Li occurs completely in the gastrointestinal tract and filtered through the glomeruli then reabsorbed in the proximal tubule which represents the primary site at which the reabsorption process occurs. It accumulates in the collecting tubule and interferes with capacity of the collecting tubule (especially the cortical portion) in both kidneys to generate cyclic adenosine monophosphate as response of stimulation of antidiuretic hormone (Erden et al 2013;Oruch et al 2014;Clos et al 2015).…”
Section: Introductionmentioning
confidence: 73%
“…6 The renal eff ects of lithium were fi rst reported more than 30 years ago, 7,8 and investigators have begun characterising and quantifying these eff ects. 6,[9][10][11] Lithium causes three types of renal impairment: acute toxic eff ects, nephrogenic diabetes insipidus, and chronic renal dysfunction. Results of a meta analysis 6 of studies addressing lithium toxicity showed that little evidence existed for a clinically signifi cant reduction in renal function in most patients, and the risk of end-stage renal failure is low.…”
Section: Introductionmentioning
confidence: 99%
“…Degenerative processes in older persons contribute to functional decline in all systems including the kidneys,7 within which sclerotic changes becomes the culprit in causing renal failure8 and chronic kidney disease 9. Apart from advanced age, duration of lithium treatment is an added risk factor for reduced glomerular filtration rate (GFR) and the subsequent deterioration of renal function 10.…”
Section: Discussionmentioning
confidence: 99%